An Alternating GluN1-2-1-2 Subunit Arrangement in Mature NMDA Receptors - Riou, Morgane; Stroebel, David; Edwardson, J. Michael; Paoletti, Pierre (PLOS ONE, 2012)
NMDA receptors (NMDARs) form glutamate-gated ion channels that play a critical role in CNS physiology and pathology. Together with AMPA and kainate receptors, NMDARs are known to operate as tetrameric complexes with four membrane-embedded subunits associating to form a single central ion-conducting pore. While AMPA and some kainate receptors can function as homomers, NMDARs are obligatory heteromers composed of homologous but distinct subunits, most usually of the GluN1 and GluN2 types. A fundamental structural feature of NMDARs, that of the subunit arrangement around the ion pore, is still controversial. Thus, in a typical NMDAR associating two GluN1 and two GluN2 subunits, there is evidence for both alternating 1/2/1/2 and non-alternating 1/1/2/2 arrangements. Here, using a combination of electrophysiological and cross-linking experiments, we provide evidence that functional GluN1/GluN2A receptors adopt the 1/2/1/2 arrangement in which like subunits are diagonal to one another. Moreover, based on the recent crystal structure of an AMPA receptor, we show that in the agonist-binding and pore regions, the GluN1 subunits occupy a “proximal” position, closer to the central axis of the channel pore than that of GluN2 subunits. Finally, results obtained with reducing agents that differ in their membrane permeability indicate that immature (intracellular) and functional (plasma-membrane inserted) pools of NMDARs can adopt different subunit arrangements, thus stressing the importance of discriminating between the two receptor pools in assembly studies. Elucidating the quaternary arrangement of NMDARs helps to define the interface between the subunits and to understand the mechanism and pharmacology of these key signaling receptors.